Digital influencer as a decision maker: moderation effects on customer attitudes towards brands and purchase intentions for products and services - Karacsonyi, Rúbia Sinhorini (2023)
Social influence plays a significant role in customer decision-making, as people are often influenced by the opinions, beliefs, and attitudes of others. In today’s digital age, companies are increasingly turning to digital influencers to spread positive endorsements and promote their products or services. However, little research has been conducted on the effects of digital influencers as active decision-makers within the organizational framework. To address this gap, this study was conducted to examine the effects of using a digital influencer as a decision-maker on customer attitudes towards brands and purchase intentions for products and services. The study drew upon existing literature on celebrity endorsement and considered factors such as credibility, attractiveness, meaning transfer, and the match-up congruence. A survey across three categories (“Alcoholic Beverages,” “Plant Based Food,” and “Finance Services”) and divided into two groups (“Non-decision Maker” and “Decision Maker”) was applied to a sample of 158 respondents experienced in social media and online platforms. Then, a regression analysis was combined with the Andrew Hayes’s Process method to test the hypothesis. The results showed that the presence of a “Decision Maker” deflated the “Attractiveness” and “Match-up Congruence” effect of the influencer, but maintained the “Brand Meaning Transference” on the relationship between “Customer Attitudes Towards Brands”. Additionally, it maintained the “Attractiveness” effect and increased the “Brand Meaning Transference” effect in the relationship between “Purchase Intentions”. These findings contribute to both theory and practice, as they shed light on the potential benefits and drawbacks of using digital influencers as decision-makers in the organizational framework.